The effectiveness of problem based learning (pbl) at intermediate financial accounting subject - Suryanti, Nunuk (Dinamika Pendidikan, 2016)
It was a quasi-experimental research to know the effectiveness of Problem Based Learning (PBL) Model comparing to Drill Model at Intermediate Financial Accounting subject. The population of this study was accounting education students in the year of 2014/2015 in FKIP Riau Islamic University/ Universitas Islam Riau (UIR) consisting of 4 classes. The samples were taken by purposive sampling. It was used PBL at the experimental classes and drill model at the controlled class. The data were collected through interview, observation, and tests (pre-test and post-test). Then; the data were analyzed by independent sample test. The results of the research showed that there was not any difference between students who taught by PBL and Drill model for their learning outcomes at Intermediate Financial Accounting.